2002
DOI: 10.1111/j.1151-2916.2002.tb00394.x
|View full text |Cite
|
Sign up to set email alerts
|

In‐Plane Polarized 0.7Pb(Mg1/3Nb2/3)O3–0.3PbTiO3 Thin Films

Abstract: Ferroelectric 0.7Pb(Mg1/3Nb2/3)O3–0.3PbTiO3 (PMN‐PT) thin films were deposited on ZrO2/SiO2/silicon substrates using a chemical‐solution‐deposition method. Using a thin PZT film as a seed layer for the PMN‐PT films, phase‐pure perovskite PMN‐PT could be obtained via rapid thermal annealing at 750°C for 60 s. The electrical properties of in‐plane polarized thin films were characterized using interdigitated electrode arrays on the film surface. Ferroelectric hysteresis loops are observed with much larger remanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Consequently many studies have focused on developing processing methodologies to avoid them. [10][11][12][13] We show here that the introduction of a PbZr 0.95 Ti 0.05 O 3 ͑PZT͒ seed layer permits a purely perovskite 0.93PMN-0.07PT film to be grown at lower annealing temperature ͑650°C͒ with a lower porosity.…”
mentioning
confidence: 99%
“…Consequently many studies have focused on developing processing methodologies to avoid them. [10][11][12][13] We show here that the introduction of a PbZr 0.95 Ti 0.05 O 3 ͑PZT͒ seed layer permits a purely perovskite 0.93PMN-0.07PT film to be grown at lower annealing temperature ͑650°C͒ with a lower porosity.…”
mentioning
confidence: 99%
“…Therefore, it is necessary to obtain PMN-PT films with pure-perovskite phase at certain low crystallization temperatures. However, previous results (Hoffmann et al, 2002;Zhou et al, 2002;Gong et al, 2004;Donnely et al, 2003) had shown that crystallization temperature was usually higher than 600 • C. Many techniques have been attempted to prepare PMN-PT films, such as the sol-gel method (Hoffmann et al, 2002;Zhou et al, 2002;Gong et al, 2004), pulsed laser deposition (PLD) (Donnely et al, 2003;Lala et al, 2004;Ho et al, 2004), metal organic chemical vapor deposition (MOCVD) (Takeshima et al, 1995;Lee et al, 2001), and 0924-0136/$ -see front matter © 2008 Elsevier B.V. All rights reserved. doi:10.1016/j.jmatprotec.2008.02.003 radio frequency magnetron sputtering (RF-magnetron sputtering) (Lee et al, 2000;Li et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the sensor performance will not be affected by interlayer defects and stray capacitance in the normal direction of the film [1]. In-plane polarized ferroelectric thin films on ZrO 2 buffered silicon substrates, which are required for high-sensitivity devices, were previously deposited by chemical solution deposition (CSD) and a subsequent high temperature annealing [2][3][4]. In order to improve film quality, the ZrO 2 buffer layer was manufactured also by pulsed laser deposition [5].…”
Section: Introductionmentioning
confidence: 99%